37.1: Distinguished Paper: A Novel Blue Phase Liquid Crystal Display Applying Wall‐Electrode and High Driving Voltage Circuit. Issue 1 (June 2015) - Tsai, Cheng‐Yeh; Yu, Fang‐Cheng; Lan, Yi‐Fen; Huang, Pu‐Jung; Lin, Szu‐Yu; Chen, Yi‐Ting; Tsao, Tzu‐I; Hsieh, Chia‐Ting; Tseng, Bo‐Shiang; Kuo, Chia‐Wei; Lin, Ching‐Huan; Kuo, Chien‐Chih; et al.
Abstract : A novel polymer‐stabilized blue phase liquid crystal display (PS‐BPLCD) using an optimized BPLC for new wall‐electrode cell structure and also new driving method has been developed. Those technologies enable BPLCDs to apply conventional source driver IC in AMLCD applications. This novel PS‐BPLCDs successfully achieved high‐performance LCDs with over 2 times higher optoelectronic properties and a superior reliability.